Serum 25-Hydroxy-Vitamin D and Vitamin B12 Levels in Childhood Alopesia Areata - Selcen Kundak; Ayşe Kutlu (Galenos Publishing House, 2021)
Objective: Alopecia areata (AA); is a sudden onset, non-scaring hair loss. Twenty percent of cases are children.Although it is thought to be related to genetic predisposition, inflammation, immunological processes or psychological triggers, its pathophysiology is still not fully understood. This study was planned to investigate the levels of serum 25-hydroxy vitamin D, vitamin B12, thyroid-stimulating hormone (TSH) and free T4 FT4) in children with AA and compare the results with age-matched healthy individuals. Methods: A retrospective medical record review was carried out in an outpatient dermatology clinic in a tertiary medical center between January 1,2013 and December 31, 2017. The study included 520 patients (ages 0-18 years) who received a clinical diagnosis of AA.106 patients with AA met the inclusion criteria.Patients in the control group (n=106) were selected among children aged 0-18 years without any medical and/or psychiatric diagnosis. Both past medical and family medical history were also noted. Results of laboratory tests including vitamin D, vitamin B12, TSH, FT4, and thyroid auto-antibodies were noted. Results: There was no significant difference between the patient and control groups in terms of mean age.Mean age of onset was 8.0 years. The number of boys and girls in both the patient and control groups were 55 and 51. Serum levels of FT4 and TSH in patients with AA were significantly higher than the control group. Both vitamin D and vitamin B12 levels of the patients with AA were significantly lower than the control group. Conclusion: Although its role in etiopathogenesis is not understood, the importance of monitoring both vitamins and thyroid functions in childhood AA cases is obvious.